2022
DOI: 10.1002/sstr.202200209
|View full text |Cite
|
Sign up to set email alerts
|

Photocyclization‐Induced Emission Enhancement and Circularly Polarized Luminescence Inversion of Achiral Emitters in Co‐Assembled Gels

Abstract: Precisely controlling the circularly polarized emission of achiral organic luminescent molecules in an aggregated state is a remaining challenge in this research field, since it should simultaneously overcome the ubiquitous issues of chirality transfer and aggregation‐caused quenching occurring in the aggregated systems. Herein, a facile and universal approach to achieving assembly‐accelerated photocyclization and photocyclization‐enhanced emission of tetraphenylethylene (TPE) derivative in the gel state is re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 52 publications
0
17
0
3
Order By: Relevance
“…The chiral compound of pPMPCC was synthesized as in our previous report and characterized by NMR and FTIR (Figure S1–S3, Supporting Information). [ 9 ] Considering that the good coordination between pyridine moiety and metal ions depicted in Figure S4, Supporting Information, the metal‐ion coordination‐driven aggregation behavior of pPMPCC and various metal ions was explored. As shown in Figure and Figure S5, Supporting Information, the uniform suspension and gel were obtained after adding Ag + and Ni 2+ into the pPMPCC solution of mixed solvents of PX/DMSO (100/1, v/v) respectively, while precipitation was observed from the mixtures after adding other metal ions such as Mn 2+ , Co 2+ , Cu 2+ , Zn 2+ , and Bi 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…The chiral compound of pPMPCC was synthesized as in our previous report and characterized by NMR and FTIR (Figure S1–S3, Supporting Information). [ 9 ] Considering that the good coordination between pyridine moiety and metal ions depicted in Figure S4, Supporting Information, the metal‐ion coordination‐driven aggregation behavior of pPMPCC and various metal ions was explored. As shown in Figure and Figure S5, Supporting Information, the uniform suspension and gel were obtained after adding Ag + and Ni 2+ into the pPMPCC solution of mixed solvents of PX/DMSO (100/1, v/v) respectively, while precipitation was observed from the mixtures after adding other metal ions such as Mn 2+ , Co 2+ , Cu 2+ , Zn 2+ , and Bi 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Liu and Zhao et al demonstrated a photo-mediated co-assembly of m / p -PMPCC and tetraphenylethylene (TPE) derivatives, showing assembly-assisted photocyclization and aggregation-enhanced CPL in co-assembled gels. 248 Upon non-covalently binding the phenyl groups of the TPE, the co-assemblies present at least three merits: (1) the photocyclization efficiency is boosted up to more than 100 fold in photo-reaction rate by confining the motion of the phenyl rings by bonding with the with carboxyl- and hydroxyl groups; (2) helical stacking of the TPE-chromophores is enforced, minimizing the π–π stacking induced luminescence quenching, and enhancing the fluorescence emission up to 105 times, leading to good CPL emission of achiral TPE-chromophores; and (3) photoreaction-mediated CPL inversion is achieved. This work provides a facile approach to developing photo-modulated CPL materials that may have potential in chiroptical optoelectronics and flexible display devices.…”
Section: Applications Of Assembled Materials With Smcimentioning
confidence: 99%
“…In 2022, Liu's group found the co‐assembled gels of TPE‐based derivative exhibited high efficiency of photocyclization and sharply enhancement of emission after the photocyclization and oxidation under ultraviolet (UV) irradiation (Figure 6b). [26] The result is attributed to the hierarchical chiral co‐assembly process driven by both hydrophobic effect and hydrogen bonding between the molecules. In addition, it also successfully achieved an unexpected CPL inversion from TPE‐based derivative after UV irradiation due to the change of dihedral angle between chromophores driven by the structural evolution of chiral aggregates.…”
Section: Induced Cpl Materials Based On Chiral Supramolecular Co‐asse...mentioning
confidence: 99%